Mouth Morphometry and Architecture of Freshwater Cat Fish Mystus vittatus Bloch (1974) (Siluriformes, Bagridae) in Relation to its Feeding Habit - Chattopadhyay, S.; Nandi, S.; Saikia, S. K. (Journal of Scientific Research, 2013)
<!–[if gte mso 9]> <![endif]–> Mouth morphology and architecture of a freshwater cat fish Mystus vittatus was studied in relation to its food and feeding habits. The fish has small mouth and predates mainly on small sized preys. It possesses terminal mouth, equipped with villiform teeth on both lower and upper jaw. Lower jaw also bears molariform teeth in addition to villiforms teeth to grasp and prevent the escape of prey. Lack of papilliform teeth and prominent microridges suggest its plankton feeding habits and poor test sensation on captured preys. Keywords: Dentition; Carnivorous; Molariform; Villiform © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i1.16369 J. Sci. Res. 6 (1), 169-174 (2014) <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>